OFDM for data distribution in phased array antennas - Barros, Sara Pena (2018)
Currently, all the control data behind the RF front-end modules in phased array radars is transmitted digitally and simultaneously by means of optical ber, resulting in a massive distribution network. The design of cheaper radars requires alternative ways of transmission to be explored. An intuitive and rather straight approach is to take advantage of the already existent RF layer used for the distribution of the radar pulse. The aim of this thesis work is to investigate OFDM as a modulation option for that approach and to determine whether or not it is a viable one. As proof of concept, experimental results are presented and discussed.